(untitled) (Mustansiria Dental Journal, 2022)
Background: Flexible dentures (thermoplastic material) are ideal alternatives to traditional methyl methacrylate dentures, since they not only give exceptional aesthetics and comfort, but also adapt to the continual movement of partially edentulous patients. During the manufacturing of acrylic denture base material, an effective separating medium must be used to separate the denture cleanly from the plaster to avoid direct contact between the denture base material and the mould surface. Objective: The goal of this study was to investigate the effect of several types of oil (glycerin oil, olive oil, and black castor oil) on the surface roughness and hardness of flexible denture base material compared with cold-mould seal separating medium.